THE VIRTUAL PUBLIC SPHERE: QUESTIONING THE STANDARDS OF FORMATION ACCORDING TO THE TRILOGY OF RECOGNITION BY AXEL HONNETH - Bouchenafa Talia; Mezzi Khadija; Maaziz Abdelkader (International Journal of Innovative Technologies in Social Science, 2025)
This study aims to investigate the extent to which cyber space is able to host public sphere discussions based on public deliberation of issues of public affairs, communicative equality between social subjects. The study attempted to search for the trilogy of recognition (love, solidarity, right) by Axel Honeth and search for it within the cyber platforms that It is relied upon as an incubating environment for public affairs discussions and the formation of a virtual public sphere that seeks to achieve mutual recognition between interacting subjects.